1989
DOI: 10.1111/j.1348-0421.1989.tb03156.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered Virulence of a Pleiotropic Staphylococcus aureus Mutant with a Low Producibility of Coagulase and Other Factors in Mice

Abstract: The virulence of a pleiotropic Staphylococcus aureus mutant with an extremely low producibility of coagulase and other factors was investigated in mouse. A mutant strain, designated as CL-1, showed the same LD50 and the same intrarenal proliferation as its parental strain, when the mutant organisms were inoculated in mice in high doses. The mutant organisms, however, showed a diminished intrarenal proliferation compared with its parental organisms in low doses. This mutant strain expressed a pleiotropic phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Coagulase activity from each strain was determined on PAF200RP plate (5 was performed by a convenient method (6) devised by our group using a commercially available set of type-specific antisera (Denka Seiken). Statistical analyses were made using the x2 test.…”
mentioning
confidence: 99%
“…Coagulase activity from each strain was determined on PAF200RP plate (5 was performed by a convenient method (6) devised by our group using a commercially available set of type-specific antisera (Denka Seiken). Statistical analyses were made using the x2 test.…”
mentioning
confidence: 99%
“…Although staphylocoagulase is classically considered to be a virulence factor, the available evidence from animal infection models is conflicting. Some studies showed decreased virulence of coagulase-negative mutants (1,7,8,12,20), but these mutant strains arose from nonspecific increased mutagenesis and probably had inherently reduced virulence compared to the nonmutant parent strain. Coagulase-negative mutants obtained by site-specific mutagenesis showed reduced virulence in a murine hematogenous pulmonary infection model (18), and inhibition of coagulase activity using inhibitory RNA reduced bacterial loads in an animal S. aureus bacteremia model (24), showing the potential of coagulase inhibition strategies in these settings.…”
mentioning
confidence: 99%
“…and i.p. LD 50 infections, and murine mastitis [112, 126129]. However the mode of mutagenesis and mutant selection may have also led to additional mutations, for example in important virulence regulatory genes.…”
Section: Introductionmentioning
confidence: 99%